Maternal roles in children’s character formation: Religious education, developmental strategies, and role modeling in Islam - Siti Robi'ah; Nur Hidayat (An-Nisa’ Journal of Gender Studies, 2023)
The strong emphasis on mothers in children’s character education may raise questions about gendered divisions of parenting responsibilities and the extent of paternal involvement. This study aims to analyze the role of mothers in children’s character education from an Islamic perspective. A qualitative library research approach was employed using thematic content analysis. Data from 35 scholarly sources published between 2014 and 2023 were analyzed through source triangulation, expert validation, and peer review. The findings reveal three interconnected dimensions of maternal roles. First, mothers function as the madrasah al-ula (first school) by introducing faith, habituating worship, and cultivating moral values from early childhood. Second, mothers employ family-based strategies for character formation, including giving meaningful names, praying for children, stimulating intellectual development, fostering independence, establishing healthy communication, and using the environment as a learning resource. Third, mothers implement Islamic character education through consistent role modeling in everyday life, reinforced by religious values concerning the dignity of motherhood and filial respect for parents. The study concludes that mothers emerge as key actors in Islamic character education through religious instruction, contextual parenting strategies, and everyday role modeling. These findings contribute to Islamic education scholarship by highlighting how maternal education integrates faith, worship, moral development, and character formation within family life, while also raising the need to consider more balanced parental involvement in contemporary family education.